Large-scale computing - Dubitzky, Werner, 1958-; Kurowski, Krzysztof, 1977-; Schott, Bernard, 1962- (Hoboken, N.J. : John Wiley & Sons, 2012)
'Complex systems modeling and simulation approaches are being adopted in a growing number of sectors, including finance, economics, biology, astronomy, and many more. Technologies ranging from distributed computing to specialized hardware are explored and developed to address the computational requirements arising in complex systems simulations.The aim of this book is to present a representative overview of contemporary large-scale computing technologies in the context of complex systems simulations applications. The intention is to identify new research directions in this field and to provide a communications platform facilitating an exchange of concepts, ideas and needs between the scientists and technologist and complex system modelers. On the application side, the book focuses on modeling and simulation of natural and man-made complex systems. On the computing technology side, emphasis is placed on the distributed computing approaches, but supercomputing and other novel technologies are also considered'--
'The aim of this book is to present a representative overview of contemporary large-scale computing technologies in the context of complex systems simulations applications'--
Includes bibliographical references and index.
Keywords: Computer simulation